Experimental study on impact on fineness of sand and M-sand in M20 grade of concrete. (2020) - Ramkumar, S.; Dineshkumar, R.
Abstract: Main objective is to study effect on mechanical properties of M20 grade concrete by varying fineness proportions of fine aggregate in both river sand and M-sand, which is one of the major constituent of concrete. In construction field fineness of fine aggregate being used is IS 4.75 mm sieve is probably used in all cases. The fine aggregate used for casting involves river sand and M-sand. The IS sieve sizes 2.36 mm and 1.18 mm were taken as alternative. The results shows increase in fineness increases the strength of concrete.